2023
DOI: 10.3390/cells12050743
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Profiling of Neutrophil Function via a High-Throughput Flow Cytometry-Based Assay

Abstract: Neutrophils are a vital component of the innate immune system and play an essential function in the recognition and clearance of bacterial and fungal pathogens. There is great interest in understanding mechanisms of neutrophil dysfunction in the setting of disease and deciphering potential side effects of immunomodulatory drugs on neutrophil function. We developed a high throughput flow cytometry-based assay for detecting changes to four canonical neutrophil functions following biological or chemical triggers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Primary human neutrophils were isolated using the EasySep™ Human Neutrophil Isolation Kit (STEMCELL Technologies), and purity and viability were assessed according to the manufacturer’s instructions. A previously published neutrophil multiparametric assay was utilized [ 30 ], which is able to determine the most prominent neutrophil effector functions, i.e. reactive oxygen species (ROS) production, degranulation (CD66b) staining, and phagocytosis.…”
Section: Methodsmentioning
confidence: 99%
“…Primary human neutrophils were isolated using the EasySep™ Human Neutrophil Isolation Kit (STEMCELL Technologies), and purity and viability were assessed according to the manufacturer’s instructions. A previously published neutrophil multiparametric assay was utilized [ 30 ], which is able to determine the most prominent neutrophil effector functions, i.e. reactive oxygen species (ROS) production, degranulation (CD66b) staining, and phagocytosis.…”
Section: Methodsmentioning
confidence: 99%
“…CD62L (L-selectin) is an adhesion marker that can identify active neutrophils. Upon neutrophil contact with an inflammatory pathogen, the cells shed CD62L, initiating the inflammatory process and activating neutrophils [35]. In the N1 subpopulation, 58.01%, 62.47%, 68.13%, 53.68%, 42.67%, and 65.39% of cells were activated in DMEM control, RPMI control, N1-polarized, N2-polarized, MCF-7 CM, and MDA-MB-231 CM, respectively; all of which were not statistically different.…”
mentioning
confidence: 99%
“…CD11b expression and CD62L cleavage indicate primed neutrophils, and the surface density of CD11b increases during the process. CD66b expression is linked with the activation of secondary granules, and increased expression is associated with increased inflammation [35,36]. Our results showed that the activated N1 population does not undergo high levels of degranulation, where 15.89%, 16.63%, 15.2%, 11.22%, 17.84%, and 13.71% of DMEM control, RPMI control, N1-polarized, N2-polarized, MCF-7 CM, and MDA-MB-231 CM were degranulating, respectively.…”
mentioning
confidence: 99%